2012
DOI: 10.48550/arxiv.1205.5555
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Pseudo-Higgs Signals a the LHC

Abstract: We consider general fermi-phobic scenarios in which excess events in diphoton or WW/ZZ resonances may be seen at LHC. These Higgs like signals do not necessarily suggest that the new resonance is a particle with Yukawa couplings nor do we know that it is responsible for electroweak symmetry breaking. We can, however, extract two facts from it, this particle couples to pairs of SU(2) and U(1) gauge bosons and it must be a scalar, pseudoscalar, or tensor. We consider the signals of general operators up to effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…We note that in addition to coupling directly to pairs of gauge field-strength tensors, LEX states may couple to pairs of weak gauge bosons by coupling to the Higgs kinetic term 𝐷 𝜇 𝐻 𝐷 𝜇 𝐻 † [17].…”
Section: Filling Out the Catalog; Phenomenological Observationsmentioning
confidence: 99%
“…We note that in addition to coupling directly to pairs of gauge field-strength tensors, LEX states may couple to pairs of weak gauge bosons by coupling to the Higgs kinetic term 𝐷 𝜇 𝐻 𝐷 𝜇 𝐻 † [17].…”
Section: Filling Out the Catalog; Phenomenological Observationsmentioning
confidence: 99%
“…Some interesting studies in a similar spirit (but asking different questions) can be found in Refs. [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…FIG.3: log 10 of the fractional difference in the rate of pp → φ → γγ between a model with κ s = 1 and κ s = 50(10), indicated by the upper (lower) curve, with κ g adjusted such that the over-all rate at √ s = 7 TeV is SM-like.…”
mentioning
confidence: 99%